THE INFLUENCE OF CREATIVE TIKTOK CONTENT AND EXTRINSIC MOTIVATION ON SPIRITUAL INTELLIGENCE(CASE STUDY OF TIKTOK CREATIVE CONTENT VIEWERS IN GROBOGAN REGENCY) - Aji Prastiya; Dita Prameswari (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2025)
Background & Purpose: The increasing consumption of motivational content on social media, particularly Tiktok, has raised questions about its impact on users' spiritual aspects. In Grobogan Regency, many Tiktok users aged 17–25 access motivational content. Some feel motivated to take positive action, while others feel distracted and become passive. This study aims to examine the influence of Tiktok's creative content and extrinsic motivation on spiritual intelligence. Method: This study employed a quantitative approach with a survey method. Purposive sampling was used to select 148 respondents aged 17–25 who actively access motivational content on Tiktok. The questionnaire was analyzed using SPSS with validity and reliability tests, multiple linear regression, t tests, and f tests. Results: The results show that Tiktok's creative content has a positive and significant effect on extrinsic motivation and spiritual intelligence. Extrinsic motivation also has a positive and significant effect on spiritual intelligence. Tiktok's creative content variable has a dominant influence over extrinsic motivation. This demonstrates that positive content on Tiktok can influence users' spiritual spirit and values. Conclusion & Suggestion: This study shows that although Tiktok creative content has an influence on extrinsic motivation and spiritual intelligence, the effect of extrinsic motivation on spiritual intelligence is not significant. The study's limited focus on aspects of extrinsic motivation, such as external encouragement (praise, advice, and environmental influences), is not able to fully describe the relationship. Therefore, further research is recommended to explore more specific types of extrinsic motivation, such as motivation to study or work, to understand their contribution to the development of spiritual intelligence. Furthermore, the use of multiple linear regression analysis is still recommended to re-examine the relationship between variables in a broader context.